The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/vaccines8020260
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of CD8+ T-Cell Responses Following Vaccination with Conserved Regions of HIV-1 in Nairobi, Kenya

Abstract: Sub-Saharan Africa carries the biggest burden of the human immunodeficiency virus type 1 (HIV-1)/AIDS epidemic and is in an urgent need of an effective vaccine. CD8+ T cells are an important component of the host immune response to HIV-1 and may need to be harnessed if a vaccine is to be effective. CD8+ T cells recognize human leukocyte antigen (HLA)-associated viral epitopes and the HLA alleles vary significantly among different ethnic groups. It follows that definition of HIV-1-derived peptides recognized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…The immune responses directed towards epitopes in conserved regions are usually subdominant but may provide protection against multiple HIV-1 subtypes [ 17 , 53 ]. Many studies that included Pol epitopes in vaccine candidates showed stimulation of effective CTL responses [ 18 , 56 , 61 , 62 ]. Ahmed et al, showed control of HIV-1 replication in vitro through stimulation of Pol CTL responses by a vaccine that contained subdominant epitopes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immune responses directed towards epitopes in conserved regions are usually subdominant but may provide protection against multiple HIV-1 subtypes [ 17 , 53 ]. Many studies that included Pol epitopes in vaccine candidates showed stimulation of effective CTL responses [ 18 , 56 , 61 , 62 ]. Ahmed et al, showed control of HIV-1 replication in vitro through stimulation of Pol CTL responses by a vaccine that contained subdominant epitopes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these observations confirm that BG505 TTT folds with a conformation closely resembling those of other nativelike Env trimers. BG505 TTT elicits qualitatively improved antibody responses in mice and rabbits Simian (chimpanzee) adenovirus-derived ChAdOx1 74 and modified vaccinia Ankara (MVA) 75 are well-established vector systems for the delivery of immunogens [76][77][78][79][80][81][82][83] . ChAdOx1 was used by AstraZeneca to deliver one of the e StrepTactinXT ELISA assay with StrepTactinXT-purified SOSIP.v8, SC and TTT protein preparations against a panel of bNAbs (2G12, VRC01, PGT121, PGT145, VRC26.25, PGT151) and non-NAbs (F105).…”
Section: Resultsmentioning
confidence: 99%
“…Simian (chimpanzee) adenovirus-derived ChAdOx1 75 and modified vaccinia Ankara (MVA) 76 are well-established vector systems for the delivery of immunogens [77][78][79][80][81][82][83][84] . ChAdOx1 was used by AstraZeneca to deliver one of the first effective SARS-CoV-2 vaccines 50 .…”
Section: Bg505 Ttt Elicits Qualitatively Improved Antibody Responses ...mentioning
confidence: 99%